Dysregulated Retinoic Acid Signaling in the Pathogenesis of Pseudoexfoliation Syndrome - Zenkel, Matthias; Hoja, Ursula; Gießl, Andreas; Berner, Daniel; Hohberger, Bettina; Weller, Julia; König, Loretta; Huebner, Lisa; Ostermann, Thomas A.; Gusek-Schneider, Gabriele; Kruse, Friedrich; Pasutto, Francesca; et al. (International Journal of Molecular Sciences, 2022)
Pseudoexfoliation (PEX) syndrome, a stress-induced fibrotic matrix process, is the most common recognizable cause of open-angle glaucoma worldwide. The recent identification of PEX-associated gene variants uncovered the vitamin A metabolic pathway as a factor influencing the risk of disease. In this study, we analyzed the role of the retinoic acid (RA) signaling pathway in the PEX-associated matrix metabolism and evaluated its targeting as a potential candidate for an anti-fibrotic intervention. We provided evidence that decreased expression levels of RA pathway components and diminished RA signaling activity occur in an antagonistic crosstalk with TGF-beta 1/Smad signaling in ocular tissues and cells from PEX patients when compared with age-matched controls. Genetic and pharmacologic modes of RA pathway inhibition induced the expression and production of PEX-associated matrix components by disease-relevant cell culture models in vitro. Conversely, RA signaling pathway activation by natural and synthetic retinoids was able to suppress PEX-associated matrix production and formation of microfibrillar networks via antagonization of Smad-dependent TGF-beta 1 signaling. The findings indicate that deficient RA signaling in conjunction with hyperactivated TGF-beta 1 /Smad signaling is a driver of PEX-associated fibrosis, and that restoration of RA signaling may be a promising strategy for anti-fibrotic intervention in patients with PEX syndrome and glaucoma.
CRIS-Team WoS Importer:2022-06-24
Keywords: pseudoexfoliation syndrome; pseudoexfoliation glaucoma; retinol; retinoic acid; extracellular matrix; fibrosis; TGF-β1

Klinische und echographische Untersuchungsbefunde bei Patienten mit Carotis-Sinus-cavernosus-Fisteln - Huebner, L.; Struffert, T.; Mardin, Christian; Engelhorn, Tobias; Holbach, L.; Weller, J.; Hohberger, Bettina; Gusek-Schneider, Gabriele (Ophthalmologe, 2021)
Background: Symptoms and clinical findings in patients with carotid-cavernous fistulas are specific. Nevertheless, they can be very mildly expressed. This study aims to point out the potential diagnostic value of ultrasound of the orbit. Methods: A total of 25 patients with a reliable angiographic diagnosis of a fistula were reviewed retrospectively. We analyzed the symptoms, clinical findings and demonstrability in ultrasound of the orbit. Results: The most common clinical findings were nerve palsy, dilation of episcleral vessels and exophthalmos. If an ultrasound had been part of the examination a dilation of the superior ophthalmic vein could be demonstrated in all cases. Conclusion: The expeditious ultrasound investigation provides valuable information for the diagnosis of red eyes which are resistant to treatment. The examiner has to consider a fistula and perform an ultrasound especially when diplopia has newly occurred. Finally, the expedient neuroimaging can be arranged.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Diplopia; Echography; Exophthalmos; Red eye; Superior ophthalmic vein

Low-dose AtropIne for Myopia Control in Children (AIM): protocol for a randomised, controlled, double-blind, multicentre, clinical trial with two parallel arms - Farassat, Navid; Böhringer, Daniel; Küchlin, Sebastian; Molnár, Fanni E.; Schwietering, Anne; Seger, Dorina; Hug, Martin J.; Knöbel, Anja Birte; Schneider-Fuchs, Sabine; Ihorst, Gabriele; Wabbels, Bettina; Beisse, Christina; et al. (BMJ Open, 2023)
INTRODUCTION: Myopia is a major cause of degenerative eye disease and increases the risk of secondary visual impairment. Mitigating its progression therefore has great potential of clinically relevant benefit as shown by using highly diluted atropine eye drops in children of Asian origin. However, limited evidence is available regarding the efficacy and safety of low-dose atropine therapy in non-Asian populations. Hence, the Low-dose AtropIne for Myopia Control in Children (AIM) study will test the efficacy and safety of 0.02% atropine vs placebo in a German population. METHODS AND ANALYSIS: AIM is a national, multicentre, prospective, randomised, placebo-controlled, double-blind trial with two parallel arms. The primary objective is to assess the efficacy of atropine 0.02% eyedrops for myopia control in children of Caucasian origin. The primary outcome is the change in cycloplegic refraction after 1 year of treatment (D/year). Secondary and tertiary outcome measures comprise the change in axial length (mm/year) in children treated with 0.02% atropine compared with placebo, the myopic progression of participants treated with 0.01% compared with 0.02% atropine (D/year and mm/year), and the safety profile of both 0.02% and 0.01% atropine. Furthermore, the myopic progression 1 year after cessation of therapy with 0.02% atropine will be evaluated. Inclusion criteria are an age of 8-12 years and myopia of -1 D to -6 D with an estimated annual myopia progression of ≥0.5 D. After randomisation, patients will receive either atropine 0.02% (arm A) or placebo eye drops (arm B) in the first year of treatment. In the second year, they will continue to receive atropine 0.02% (arm A) or switch to atropine 0.01% (arm B). In the third year, they will switch to placebo (arm A) or continue with atropine 0.01% (arm B). To achieve a statistical power of 80%, the calculated sample size is 300. The trial has started in October 2021 with a planned recruitment period of 18 months. ETHICS AND DISSEMINATION: AIM has been approved by the Central Ethics Committee of the University Medical Center Freiburg (21-1106), local ethics committees of each participating centre and the German Federal Institute for Drugs and Medical Devices (61-3910-4044659). It complies with the Declaration of Helsinki, local laws and ICH-GCP. Results and underlying data from this trial will be disseminated through peer-reviewed publications and conference presentations. TRIAL REGISTRATION NUMBER: NCT03865160.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Clinical trials; Medical ophthalmology; OPHTHALMOLOGY; Paediatric ophthalmology